2015
DOI: 10.1371/journal.pone.0117480
|View full text |Cite
|
Sign up to set email alerts
|

Normal Range of Hepatic Fat Fraction on Dual- and Triple-Echo Fat Quantification MR in Children

Abstract: ObjectivesTo evaluate hepatic fat fraction on dual- and triple-echo gradient-recalled echo MRI sequences in healthy children.Materials and MethodsWe retrospectively reviewed the records of children in a medical check-up clinic from May 2012 to November 2013. We excluded children with abnormal laboratory findings or those who were overweight. Hepatic fat fraction was measured on dual- and triple-echo sequences using 3T MRI. We compared fat fractions using the Wilcoxon signed rank test and the Bland-Altman 95% l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…Occasionally, fat-/water swaps occurred, especially in the liver dome (segment VII/VIII), but no ROIs were drawn in these regions for the purpose of the current study. We used a dual-echo sequence for fat quantification which is prone to potentially confounding T1 and T2* relaxation effects [ 38 , 39 ], but a recent paper [ 40 ] showed no difference in dual fat fraction and triple fat fraction in healthy children with a mean value of 2.3±2.0% on dual-echo MRI and 2.9±1.4% on triple-echo MRI. Dual-echo imaging was shown to measure lower FSF values in patients with pathological liver iron deposition [ 41 ], an effect, which in part may be corrected with multi-echo imaging [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Occasionally, fat-/water swaps occurred, especially in the liver dome (segment VII/VIII), but no ROIs were drawn in these regions for the purpose of the current study. We used a dual-echo sequence for fat quantification which is prone to potentially confounding T1 and T2* relaxation effects [ 38 , 39 ], but a recent paper [ 40 ] showed no difference in dual fat fraction and triple fat fraction in healthy children with a mean value of 2.3±2.0% on dual-echo MRI and 2.9±1.4% on triple-echo MRI. Dual-echo imaging was shown to measure lower FSF values in patients with pathological liver iron deposition [ 41 ], an effect, which in part may be corrected with multi-echo imaging [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Subjects were divided into three groups. One was the normal group, for those who had normal MR proton density fat fraction (PDFF) of the liver (< 6% according to a previous study)[ 13 ], normal body mass index, and normal transient elastography (TE) results when they had TE results within one year of MRI examinations. The second was the fatty liver (FAT) group, for subjects who had PDFF greater than 6%.…”
Section: Methodsmentioning
confidence: 99%
“…The complexity tends to increase considering a wider age-range. Accordingly, it has been found that in non-obese children the median fat fraction was 1.6%-2.7% up to a maximum of 6.5–8.0% dependent on whether measured using dual or triple echo gradient-recalled echo sequence MRI11. Another study performed on obese children without NAFLD found a mean hepatic fat fraction of 2.0% up to a maximum of 4.69%12.…”
mentioning
confidence: 97%